2006
DOI: 10.1111/j.1365-313x.2006.02738.x
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression profiles of Arabidopsis Cvi seeds during dormancy cycling indicate a common underlying dormancy control mechanism

Abstract: SummaryPhysiologically dormant seeds, like those of Arabidopsis, will cycle through dormant states as seasons change until the environment is favourable for seedling establishment. This phenomenon is widespread in the plant kingdom, but has not been studied at the molecular level. Full-genome microarrays were used for a global transcript analysis of Arabidopsis thaliana (accession Cvi) seeds in a range of dormant and dry after-ripened states during cycling. Principal component analysis of the expression patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
537
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(574 citation statements)
references
References 80 publications
29
537
1
7
Order By: Relevance
“…Cvi seeds tend to germinate more readily at lower temperatures, consistent with a winter-annual phenotype, while Bur seeds show the reverse response and germinate more readily at higher temperatures consistent with a summer-annual phenotype. In addition, short periods of low temperature (58C) appeared to be an efficient way to release dormancy of Bur but not Cvi, which first requires a period of AR to become sensitive to low temperature (Cadman et al, 2006;Finch-Savage et al, 2007). Germination of Ler seeds produced at 208C had high germination at low temperatures coupled to high-temperature thermodormancy.…”
Section: Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Cvi seeds tend to germinate more readily at lower temperatures, consistent with a winter-annual phenotype, while Bur seeds show the reverse response and germinate more readily at higher temperatures consistent with a summer-annual phenotype. In addition, short periods of low temperature (58C) appeared to be an efficient way to release dormancy of Bur but not Cvi, which first requires a period of AR to become sensitive to low temperature (Cadman et al, 2006;Finch-Savage et al, 2007). Germination of Ler seeds produced at 208C had high germination at low temperatures coupled to high-temperature thermodormancy.…”
Section: Temperaturementioning
confidence: 99%
“…For example, the ratio of red/far red wavelengths alters as light passes through a leaf canopy, informing about the presence of competing plants (as reviewed in Pons, 2000). In Arabidopsis, dormancy release and the completion of germination of both summer-and winter-annual ecotypes can have an absolute light dependency (Cadman et al, 2006;Finch-Savage et al, 2007;Footitt et al, 2013).…”
Section: Light As a Spatial Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). Recently, by using a strongly dormant Arabidopsis accession, Cape Verde Islands (Cvi), Cadman et al (2006) reported that expression of NCED6 is up-regulated in primary dormant and secondary dormant seeds imbibed in the dark. Seo et al (2006) reported that NCED6 expression in seeds is induced during dark imbibition after farred light treatment and suppressed by subsequent red-light treatment.…”
Section: Regulation Of Aba Biosynthesis By High Temperature In Seedsmentioning
confidence: 99%
“…Instead of burial, stratification and hormones also dry storage (after-ripening) of seeds can release dormancy in several plant species e.g., Amaranthus retroflexus (Schön-beck and Egley 1980), Arabidopsis thaliana (Cadman et al 2006), Hordeum vulgare (Gubler et al 2008), Sisymbrium officinale (Iglesias-Fernandez and Matilla 2009) and Avena fatua ). Moreover, nitrogen-containing compounds such as nitrate, nitrite, hydroxylamine and azide have been known to break dormancy of seeds (Hendricks and Taylorson 1974).…”
Section: Introductionmentioning
confidence: 99%